Cowpea Bean (Vigna unguiculata L. Walp): socioeconomic and technological perspective in the Colombian Caribbean: Economic and technological analysis of Caupí bean productio - MARTINEZ REINA, Antonio Maria; Tordecilla Zumaque, Lilibeth; Grandett Martínez, Lina María; Rodríguez Pinto, María del Valle; Cordero Cordero, Carina Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this study, local technology and socioeconomic aspects of the Caupí bean production system in the producing regions of the Colombian Caribbean were characterized. To do this, structured surveys and a consensus cost workshop were applied to 30 producers selected through simple random sampling.  The information obtained was analyzed using descriptive frequency statistics, contingency tables, and correlation analyzes. The results showed that the crop is planted by small producers on an average of 1.1 hectares. The average age of farmers is 55 years with more than 11 years of experience in cultivation. The predominant production system is monoculture in 78% of the surveyed sample, yields reach 1.7 t ha-1, 90% of which production is destined for the local market. he value of labor constitutes 60% of production costs since the tasks are predominantly done manually. The profitability is 19%, the break-even point is reached with 84% of the production, leaving a remaining 16% as profit. The results achieved will be useful for entities focused on promoting production, policy planners and the formulation of research agendas in cowpea beans.